PEMBUATAN SENTRIFUG GEOTEKNIS DI UNIVERSITI KEBANGSAAN MALAYSIA (UKM) UNTUK KAJIAN LINGKUNGAN - -, Muchlis; -, Sukandarrumidi; Wan Yaacob, Wan Zuhairi; Mukhlisin, Muhammad (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Many researchers were conducted using geotechnical sentrifug in studies of the environment. The advantages of using a geotechnical sentrifug are quick to obtain the results, less materials used, economical and can be controlled for factors that are not required in the test. All geotechnical sentrifugs that were conducted are located outside from Indonesia and Malaysia, so that requires for build a geotechnical sentrifug in the country. Engineering methodology was to modify the existing geotechnical sentrifug in other countries. The geotechnical sentrifug that was build Universiti Kebangsaan Malay-sia is 50 cm radius beam type geotechnical sentrifug with dead lock capacity 6 kg and maximum acceleration around 75 gravity. The main components are body, arm, bucket sample, counter weight, motor, contaminant bottle and computer. The geo-technical sentrifug is equipped with speed sensor, close sensor, stroboscope sensor and vibration sensor. This geotechnical sentrifug was conducted in environmental studies.